1971
DOI: 10.1071/bi9710007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Studies with Banana Fruit Slices I. Changes in the Incorporation of 14c Labelled Compounds in Response to Cutting

Abstract: SummaryTransverse slices of green banana fruit were vacuum-infiltrated with aqueous solutions of 14C-labelled metabolites and the non-metabolite a-methyl-D-glucoside immediately after cutting, and at 17 hr after cutting-i.e. near the peak of "induced" respiration.The The rate of uptake of acetate and malonate is rapid in slices both at 0 and 17 hrafter cutting, wheras the rate of uptake of citrate and D-glucose is low at 0 hr but rapid at 17 hr after cutting. a-Methyl-D-glucoside is taken up at a low and simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…1C). Respiration rates have been reported to increase in response to ethylene treatment in fruits (Frenkel et al, 1968;McGlasson et al, 1971) and roots (Kahl and Laties, 1989). Ethylene can enhance respiration via the alternative respiration pathways (Esashi et al, 1987) and increase tissue ATP content through mobilization of AMP or ADP (Perl, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…1C). Respiration rates have been reported to increase in response to ethylene treatment in fruits (Frenkel et al, 1968;McGlasson et al, 1971) and roots (Kahl and Laties, 1989). Ethylene can enhance respiration via the alternative respiration pathways (Esashi et al, 1987) and increase tissue ATP content through mobilization of AMP or ADP (Perl, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ethylene production (McGlasson 1969), of carbon metabolism (Palmer and McGlasson 1969;Brady et al 1970a;McGlasson et al 1971), of protein biosynthesis (Brady et al 1970b), and of the effects of plant growth substances (Vendrell 1969(Vendrell , 1970Wade and Brady 1971) have been made using these slices.…”
Section: Introductionmentioning
confidence: 99%
“…McGlasson et al (12) and Frenkel et al (8) found that they could inhibit ripening of thick banana slices and Bartlett pear fruit, respectively, with cycloheximide but not the respiratory climacteric. Quazi and Freebairn (16) found that bananas ripened normally under diminished 02 tension, while having a much reduced respiratory climacteric.…”
mentioning
confidence: 99%
“…Although an increase in protein synthesis in several climacteric fruits has been demonstrated, its importance to the ripening process has been questioned (23). Brady and O'Connell (4) exposed 6-mm thick cross sections of banana fruit to 5 AI/I ethylene for 6 h and observed an increase in protein synthesis without concomitant ripening; however, when the sections were exposed to ethylene for 12 h, enhanced protein synthesis was accompanied by ripening. Upon analyzing in vivo-labeled protein samples on polyacrylamide gels, they found that the increase in protein synthesis with 24 h of ethylene treatment was not limited ' Supported by Research Grant GM 19807 from the United States Public Health Service.…”
mentioning
confidence: 99%